Intestinal Parasitic Infections, Treatment and Associated Factors among Pregnant Women in Sao Tome and Principe: A Cross-Sectional Study - Alexandra Vasconcelos; Swasilanne Sousa; Nelson Bandeira; Marta Alves; Ana Luísa Papoila; Filomena Pereira; Maria Céu Machado (Journal of Tropical Medicine)
Background. Intestinal parasitic infections (IPIs) are a public health problem in developing countries such as Sao Tome and Principe (STP) although the pregnancy burden of IPIs is unknown in this endemic country. Thus, the aim of this study was to determine the prevalence of IPIs, prescribed anthelmintics, and associated factors among pregnant women admitted to Hospital Dr. Ayres de Menezes (HAM). Methods. A hospital-based cross-sectional study was conducted among pregnant women admitted to the HAM who had undergone antenatal copro-parasitological screening. Data were abstracted from antenatal care (ANC) cards regarding parasitological results and anthelmintic prescriptions. A structured questionnaire face-to-face interview was also applied. Pregnant women with an IPI (210) were compared to noninfected women (151). Data analysis was performed using SPSS version 25.0. Odds ratios (ORs) with 95% confidence intervals (CIs) for factors associated with IPIs were estimated using multiple logistic regression models. A p value <0.05 was considered statistically significant. Results. A total of 361 participants (210 IPI and 151 no-IPI) with a mean age of 26.96 (SD: 7.00) were included. The overall prevalence of IPI was 58.2% (95% CI 52.9 to 63.3), mainly due to helminthiasis, with a 55.9% (95% CI 50.7–61.2%) rate. Ascaris lumbricoides (90.9%) was the most predominant parasite species identified followed by Trichuris trichiura (13.8%). Polyparasitism was observed in 25 cases (11.9%). Anthelmintics were prescribed to 23% of pregnant women. S intercalatum (11) and E histolytica (7) infections were not adequately treated. IPI was significantly associated with primary education (AOR 1.73 (95% CI: 1.10–2.71)), unemployment (AOR 1.94 (95% CI: 1.20–3.13)), and parity of five or above (AOR 3.82 (95% CI: 1.32–11.08)). Conclusion. This study highlights the IPI burden, associated factors, and missing treatment opportunities among pregnant women with STP. This study is a useful tool for policymakers in STP to enhance the health of women and their unborn babies.